Health Challenges Experienced by Widows in Low- and Middle-Income Countries: A Systematic Review - Neema Florence Vincent Mosha; Patrick Ngulube (Indigenous: Jurnal Ilmiah Psikologi, 2024)
This systematic review aims to critically examine empirical studies conducted in low- and middle-income countries (LMICs) to identify and analyze the diverse health challenges widows face. Specifically, the review aims to explore the psychological factors impacting their well-being and assess these challenges' implications for health outcomes. The research encompassed articles published between 2012 and 2024, sourced from PubMed, Web of Science, Scopus, and Taylor and Francis databases and the Google Scholar search engine. A total 101,889 papers were initially screened, ultimately culminating in the inclusion of sixteen papers following a meticulous evaluation and screening process. The findings revealed that widows commonly experience health challanges. In this review health challenges is presented into two major themes: mental health challenges such as depression, anxiety and stress, often stemming from emotional distress and social isoloation. The other theme is the physical health challenges that indicates a high prevalence of chronic diseases and malnutrition duet o financial instability. The study also identified several psychological factors, notably finansial insecurity, contributing to heightened stress and anxiety, further complicating their mental health. Many widows also face diminished social support leading to increased feelings of loneliness and stigma, while economic hardship significantly limits their access to healthcare and basic needs. Overall, these findings highlight the complex interplay of mental, physical and social factors, including critical psychological dimensions that affects the well-being of widows worldwide. This review was registered as PROSPERO 2022 CRD42022382703 with minor modifications.